2017
DOI: 10.2334/josnusd.16-0593
|View full text |Cite
|
Sign up to set email alerts
|

The effects of essential oil, povidone-iodine, and chlorhexidine mouthwash on salivary nitrate/nitrite and nitrate-reducing bacteria

Abstract: Dietary nitrate is reduced to nitrite and nitric oxide by microbial flora, and this activity is beneficial to vascular health. It has been reported that this bacterial process is inhibited by chlorhexidine mouthwash, although the effects of other products are largely unknown. This study examined the effects of several treatments on salivary nitrate/nitrite and nitrate-reducing bacteria. Twelve university staff and students performed mouth-washing with water (control), essential oil, 0.35% povidone-iodine, or 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The daily use of chlorhexidine mouthwash, even at a low concentration of 0.0025%, may reduce the count of Veillonella dispar and inhibit nitrate-reducing activity but it does not affect salivary nitrite production. Essential oil and povidone-iodine mouthwash has proven to have little effect on nitrate-reducing activity [ 73 , 74 ]. On the contrary, Senkus et al reported that 0.2% chlorhexidine mouthwash twice a day resulted in a significant reduction in salivary and plasma nitrite with a concomitant rise in salivary and plasma nitrate concentrations.…”
Section: Effects Of Antiseptic Mouthwash On Oral Microbiota and Bpmentioning
confidence: 99%
“…The daily use of chlorhexidine mouthwash, even at a low concentration of 0.0025%, may reduce the count of Veillonella dispar and inhibit nitrate-reducing activity but it does not affect salivary nitrite production. Essential oil and povidone-iodine mouthwash has proven to have little effect on nitrate-reducing activity [ 73 , 74 ]. On the contrary, Senkus et al reported that 0.2% chlorhexidine mouthwash twice a day resulted in a significant reduction in salivary and plasma nitrite with a concomitant rise in salivary and plasma nitrate concentrations.…”
Section: Effects Of Antiseptic Mouthwash On Oral Microbiota and Bpmentioning
confidence: 99%
“…Although there is compelling evidence supporting the role of the tongue microbiome in the enterosalivary nitrate-nitrite-NO pathway, this remains a relatively unexplored area of human-microbial mutualism and many important questions must be addressed. Previous studies have demonstrated that nitrite-induced reductions in blood pressure are inhibited by antiseptic chlorhexidine (CHX) or other antibacterial mouthwashes (Tannenbaum et al, 1976; Govoni et al, 2008; Petersson et al, 2009; Kapil et al, 2013; McDonagh et al, 2015; Woessner et al, 2016; Mitsui and Harasawa, 2017). The focus of these studies has been from the perspective of cardiovascular physiology, and little information is available regarding the oral health status or habits of subjects in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is also concern that PVP-I may have unknown effects on the microbial flora of the oral cavity [23]. PVP-I showed no deleterious effect on a representative nitrate-reducing species called Veillonella dispar in the oral cavity suggesting it may not have an effect on the normal oral microbial flora [24].…”
Section: Pvp-i (Betadine)mentioning
confidence: 99%
“…A Listerine product consisting of eucalyptol 0.092%, menthol 0.042%, methyl salicylate 0.060% and thymol 0.064%, in 25% ethanol has been reported to have no detrimental effect to the representative nitrate-reducing bacteria V. dispar of the mouth [24]. No toxicity, or deleterious effects on the oral microbiota have been reported for occasional use.…”
Section: Alcohol and Essential Oilsmentioning
confidence: 99%